Body Weight and Body Image - McFarlane Traci; Olmsted Marion P (BMC, 2004)
Abstract Health Issue Body weight is of physical and psychological importance to Canadian women; it is associated with health status, physical activity, body image, and self-esteem. Although the problems associated with overweight and obesity are indeed serious, there are also problems connected to being underweight. Weight prejudice and the dieting industry intensify body image concerns for Canadian women and can have a major negative impact on self-esteem. Key Findings Women have lower BMIs than men, a lower incidence of being overweight and a higher incidence of being underweight. However, women across all weight categories are more dissatisfied with their bodies. Sixty percent of women are inactive, and women with a BMI of 27 or higher are more likely to be inactive than women with lower BMIs. The data show that women are aware of the health benefits of exercise, but there is a gap between knowledge and practice. When asked about barriers to health improvement, 39.7% of women cited lack of time and 39.2% lack of willpower. Data Gaps and Recommendations Weight prejudice must be made unacceptable and positive body image should be encouraged and diversity valued. Health policies should encourage healthy eating and healthy activity. Health curricula for young students should include information about healthy eating, active lifestyle, and self-esteem. Physical activities that mothers can participate in with their families should be encouraged. Research should be funded to elucidate the most effective methods of getting women to become and remain physically active without focusing on appearance.